2009
DOI: 10.1111/j.1476-5381.2009.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional evidence for the expression of P2X1, P2X4 and P2X7 receptors in human lung mast cells

Abstract: Background and purpose: P2X receptors are widely expressed in cells of the immune system with varying functions. This study sought to characterize P2X receptor expression in the LAD2 human mast cell line and human lung mast cells (HLMCs). Experimental approach: Reverse transcriptase polymerase chain reaction (RT-PCR) and patch clamp studies were used to characterize P2X expression in mast cells using a range of pharmacological tools. Key results: RT-PCR revealed P2X1, P2X4 and P2X7 transcripts in both cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
93
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 67 publications
12
93
2
2
Order By: Relevance
“…Human lung mast cells (HLMC) were reported to express mRNA transcripts for P2X1 and P2X4 but not for P2X2, P2X3, and P2X5-P2X7 [213] in a study that did not investigate the P2Y receptor family, while others found that of the 3 P2 receptor transcripts assessed in the study, P2Y 1 and P2Y 2 but not P2X7 were expressed [200]. In contrast to the absence of the P2X7 receptor in above mentioned studies, Wareham et al reported its presence in HLMC next to P2X1 and P2X4 [214] (Table 1). Also, the human mast cell line HMC-1 was shown to highly express the P2X7 receptor being further upregulated upon PMA (phorbol 12-myristate 13-acetate) or ionomycin stimulation [200], while Wareham et al also confirmed the presence of P2X7 receptors next to P2X1, P2X4, and P2X6 in the LAD2 human cell line [214].…”
Section: Mast Cellsmentioning
confidence: 42%
See 2 more Smart Citations
“…Human lung mast cells (HLMC) were reported to express mRNA transcripts for P2X1 and P2X4 but not for P2X2, P2X3, and P2X5-P2X7 [213] in a study that did not investigate the P2Y receptor family, while others found that of the 3 P2 receptor transcripts assessed in the study, P2Y 1 and P2Y 2 but not P2X7 were expressed [200]. In contrast to the absence of the P2X7 receptor in above mentioned studies, Wareham et al reported its presence in HLMC next to P2X1 and P2X4 [214] (Table 1). Also, the human mast cell line HMC-1 was shown to highly express the P2X7 receptor being further upregulated upon PMA (phorbol 12-myristate 13-acetate) or ionomycin stimulation [200], while Wareham et al also confirmed the presence of P2X7 receptors next to P2X1, P2X4, and P2X6 in the LAD2 human cell line [214].…”
Section: Mast Cellsmentioning
confidence: 42%
“…In contrast to the absence of the P2X7 receptor in above mentioned studies, Wareham et al reported its presence in HLMC next to P2X1 and P2X4 [214] (Table 1). Also, the human mast cell line HMC-1 was shown to highly express the P2X7 receptor being further upregulated upon PMA (phorbol 12-myristate 13-acetate) or ionomycin stimulation [200], while Wareham et al also confirmed the presence of P2X7 receptors next to P2X1, P2X4, and P2X6 in the LAD2 human cell line [214]. Among the P2Y receptors, the presence of P2Y 1 , P2Y 2 , P2Y 11 , P2Y 12 , and P2Y 13 subtypes were shown by RT-PCR on cord blood-derived human mast cells (hMCs) [23].…”
Section: Mast Cellsmentioning
confidence: 67%
See 1 more Smart Citation
“…P2X receptors have been implicated in the participation of the immune system in inflammatory pain [88,89]. P2X1, P2X4, P2X7, and perhaps P2X3 receptors are expressed by mast cells [90,91]. Mast cells were the cell type in which the properties of the P2X7 receptor were initially observed and characterized by Cockcroft and Gomperts [92].…”
Section: Immune Cells and Inflammationmentioning
confidence: 99%
“…The roles of P2 receptors in mast cell biology have recently been reviewed [7]. The expression and some functions of human P2X receptors have recently been characterized using both LAD2 mast cells and human lung mast cells [8]. Nucleotides, especially adenosine 5′-diphosphate (ADP) and adenosine 5′-triphosphate (ATP), have been studied previously in the context of mast cell degranulation [9,10], but specific receptor subtypes mediating these functions have not been systematically explored.…”
Section: Introductionmentioning
confidence: 99%